Mutational Analysis of Active Site Residues Essential for Sensing of Organic Hydroperoxides by Bacillus subtilis OhrR - Soonsanga, Sumarin (American Society for Microbiology, 2007)
Bacillus subtilis OhrR is the prototype for the one-Cys family of organic peroxide-sensing regulatory proteins. Mutational analyses indicate that the high sensitivity of the active site cysteine (C15) to peroxidation requires three Tyr residues. Y29 and Y40 from the opposing subunit of the functional dimer hydrogen bond with the reactive Cys thiolate, and substitutions at these positions reduce or eliminate the ability of OhrR to respond to organic peroxides. Y19 is also critical for peroxide sensing, and the Ala substitution mutant (OhrR Y19A) is less susceptible to oxidation at the active site C15 in vivo. The Y19A protein also displays decreased sensitivity to peroxide-mediated oxidation in vitro. Y19 is in van der Waals contact with two residues critical for protein function, F16 and R23. The latter residue makes critical contact with the DNA backbone in the OhrR-operator complex. These results indicate that the high sensitivity of the OhrR C15 residue to oxidation requires interactions with the opposed Tyr residues. Oxidative modification of C15 likely disrupts the C15-Y29′-Y40′ hydrogen bond network and thereby initiates conformational changes that reduce the ability of OhrR to bind to its operator site.